Community-based dengue control intervention in Ouagadougou: intervention theory and implementation fidelity - Diane Saré; Dennis Pérez; Paul-André Somé; Yamba Kafando; Ahmed Barro; Valéry Ridde (BMC, 2018)
Abstract Background While malaria control is the primary health focus in Burkina Faso, the recent dengue epidemic calls for new interventions. This paper examines the implementation fidelity of an innovative intervention to control dengue in the capital Ouagadougou. Methods First we describe the content of the intervention and its theory. We then assess the fidelity of the implementation. This step is essential as preparation for subsequent evaluation of the intervention's effectiveness. Observations (n = 62), analysis of documents related to the intervention (n = 8), and semi-structured interviews with stakeholders (n = 18) were conducted. The collected data were organized and analyzed using QDA Miner. The theory of the intervention, grounded in reported good practices of community-based interventions, was developed and discussed with key stakeholders. Results The theory of the intervention included four components: mobilization and organization, operational planning, community action, and monitoring/evaluation. The interactions among these components were intended to improve people's knowledge about dengue and enhance the community's capacity for vector control, which in turn would reduce the burden of the disease. The majority of the planned activities were conducted according to the intervention's original theory. Adaptations pertained to implementation and monitoring of activities. Conclusions Despite certain difficulties, some of which were foreseeable and others not, this experience showed the feasibility of developing community-based interventions for vector-borne diseases in Africa.